Voluntary environmental regulation and export performance of Chinese solar energy industry - Sun, Ying; Lou, Jingyi; Sun, Huaping; Pan, Ting (Frontiers in Energy Research, 2023)
The shortage of traditional fossil energy resources, together with the pressure of environmental pollution, has stimulated the growing trade of solar energy products in China. The purpose of this article is to examine the impact of voluntary environmental regulation on China's solar energy industry trade flows. To this aim, the paper selects panel data of Chinese solar energy industry exports to 46 countries from 2002 to 2020 and uses the fixed effect regression model. The results show that export destination countries' voluntary environmental regulation has a significant positive impact on China's exports, whereas the bilateral gap in voluntary environmental regulation has a negative effect. Further evidence suggests that reducing the bilateral gap in voluntary environmental regulation has more obvious promoting effect of the exports to developed countries than to developing countries, verifying that there is country heterogeneity. Besides, more trade friction weakens the role of the host countries' voluntary environmental regulations in promoting exports. The implication of this paper is that voluntary environmental regulation have economic effects including demand effect, information effect and the common language effect, which is incredibly significant to promoting the sustained and stable development of the solar energy trade.